2007
DOI: 10.1142/s0192415x07004618
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oculo-Acupuncture on Acute Hepatic Injury Induced by Carbon Tetrachloride in Dogs

Abstract: We investigated the therapeutic effect of oculo-acupuncture on dogs induced with acute hepatic injury. Hepatic injury was induced by intraperitoneal injection with carbon tetrachloride (CCl(4)) in 8 mongrel dogs (4 females and 4 males, aged 2 to 4 years). The dogs were divided into the control group (4 dogs) and the experimental group (4 dogs). The experimental group was treated with oculo-acupuncture at the liver/gallbladder regions plus the zhong jiao region of the eye after the induction of hepatic injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Furthermore, EA exerts an anti-inflammatory effect by reducing the levels of tumor necrosis factor-α (TNF-α) (33). Research has shown that periorbital acupuncture reduced the severity of a chemically induced renal injury in animals (34). More importantly, acupoint massage acts as a non-invasive technique that can boost energy levels, and improve an individual's health and comfort.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, EA exerts an anti-inflammatory effect by reducing the levels of tumor necrosis factor-α (TNF-α) (33). Research has shown that periorbital acupuncture reduced the severity of a chemically induced renal injury in animals (34). More importantly, acupoint massage acts as a non-invasive technique that can boost energy levels, and improve an individual's health and comfort.…”
Section: Discussionmentioning
confidence: 99%